Strategi Komunikasi Persuasif Driver Grab Dalam Menjaga Minat Pengguna Aplikasi Grab di Kota Medan - Muhammad Fadri (KESKAP: Jurnal Kesejahteraan Sosial, Komunikasi dan Administrasi Publik, 2022)
The purpose of this study is to find out how the driver's persuasive communication strategy is to maintain the interest of grab application users in Medan City. The research method used in this research is qualitative. The informants in this study were Medan City Grab drivers and Grab application users in Medan City. The results of this study illustrate that persuasive communication that occurs between Grab drivers and customers is formed by an action. This is clearly shown by the actions of Grab drivers who are friendly, polite and do not disappoint customers. The factors that encourage customers to use the Grab application in the Medan City area include being very easy to access and very helpful for customers in terms of ordering food and traveling, and the rates offered are quite cheap with promos. Meanwhile, the inhibiting factor for Grab is the limited period of promos and long restaurants in preparing orders.